Impacts of natural frequency and relative stiffness of stiffened plate on nonlinear dynamic response - Wei JIANG; Guangwei HAN; Yan ZHANG (Zhongguo Jianchuan Yanjiu, 2023)
Objectives This paper studies the influence of impact load on the dynamic response of marine stiffened plates. MethodsAccording to the relevant specifications and references, the sizes of hull stiffened plates are determined. Finite element software ANSYS is used for modeling with Shell 181 element. The load is applied uniformly on the surface of the stiffened plate, and its boundary condition is fixed. The impacts of the natural frequency and relative stiffness of the stiffened plate on its nonlinear dynamic response under impact load are then analyzed. ResultsThe results show that the piecewise function relations expression of natural frequency and deflection response are obtained according to the different influences of geometric dimensions. The relative stiffness of the stiffened plate affects its deformation mode, and the critical values are 0.2 and 19. ConclusionsThese quantitative conclusions have important reference value for the safety evaluation of hull structures.